THE IMPACT OF MODULAR PRODUCT TOWARDS COST AND FLEXIBILITY PERFROMANCE AMONG MANUFACTURING FIRM IN NORTHERN MALAYSIA - Nasir, Siti Muyassarah Abd; Ahmad, Mohd Akhir Hj (CENTRAL ASIA AND THE CAUCASUS, 2024)
Nowadays, modular product production approach adopted by a firm to achieve cost- effective in market, continuous increasing in production, improve process performance and to stay in competitive globally. Referring to [1] inflation rate, employment growth and production growth are the basic indicators from economists’ view as determinants of business performance to bring significant contribution toward a nation’s economic growth. Competitive capabilities which are cost, and flexibility would be achieve through the process of planning, implementing and controlling the operation process to fulfill customer requirement [2]. This paper aim is to determine the impact of modular product towards competitive capabilities in terms of cost and flexibility because more than one-decade, modular product has been an area of interest among businesses for achieving competitive advantage. The purpose of this paper is to examine the relationship between modular product and cost then, to examine the relationship between modular product and flexibility. This paper attempt to explore the significant of modular product in the manufacturing firm with hoping that the knowledge of this study will deliver valuable contributions to business organization in developing impressive modular design strategies and manufacturing modular product to improve organization efficiency and effectiveness.